Simplified Indirect Bonding Technique for Lingual Retainer Fabrication - Fırat Öztürk; Hasan Babacan; Tolga Topçuoğlu (Galenos Yayinevi, 2012)
Aim:The aim of this study was to describe a simplified technique for fabricating an indirectly bonded lingual retainer using a light cure composite resin and clear tape.Subjects and Methods:Lingual retainers, made of dead soft wire, were bended to the lingual contour of the lower incisors on the stone models of patients and placed to the mouth. Fabricating lingual retainers with this method were used in 6 patients who were followed for 6 months.Results:During this period, failures occurred in 2 teeth. One failure was on a canine; the other one is on an incisor.Conclusion:Due to the isolation done with a clear tape in this method, there is no need for an extra procedure for the removal of the remnants of the separating medium from the resin surface. These extra procedures applied can cause the degradation of the resin surface which may lead to bonding failures